THE REGISTER AS A MEANS OF IMPROVING THE QUALITY OF MUCOVISCIDOSIS PATIENTS’ TREATMENT - I. K. Asherova; N. I. Kapranov (Педиатрическая фармакология)
The creation of a register of mucoviscidosis (MV) patients is necessary for determining the epidemic situation in the region, evaluating the efficacy of therapeutic strategies and the quality of healthcare provided. The regional register of Yaroslavl contains information about 53 MV patients. The average age of these patients is 12.9 years, the amount of patients older than 18 is 22.7%, the average age of diagnosis is 3.4 years. The overall survival median is 26.8 years (by the beginning of 2012). The prevalence of the disease is 1:8005 newborns according to the results of neonatal screening. The amount of patients infected with Pseudomonas aeruginosa and Burkholderia cepacia is 30,2% and 2,5% respectively. The F508del mutation occurs in 43,4% of all cases. The next most prevalent mutations are N1303K, 394delTT, CFTRdele2,3 (21kb) (4,72% each), the number of unidentified mutations is only 8.49%. A comparative evaluation of therapeutic approaches (basic therapy) was conducted in the Yaroslavl region and in a number of European countries. Data obtained from the register allows to solve not only clinical and epidemiological problems, but also sort out organizational issues, plan medicine provisions and conduct medical and social rehabilitation.